Pengaruh Manajerial Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru di Sekolah Menengah Kejuruan (SMK) Hikari Kabupaten Bandung Barat - Julianti, Kania Puja; Hadad, Alwi Al (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
In principle, educational institutions are formal representatives who have authority over staff, students and the surrounding environment.  In contrast, principals can act as managers, supervisors, instructors, administrators, leaders, and innovators.  Improving the quality, efficacy and efficiency of education is the main goal of educational management, which is very important in implementing education.  The implementation of education needs to be carefully planned through stages which include organizing, directing, supervising and planning so that it can function smoothly and produce quality results.  This scientific research aims to determine the managerial leadership of school principals on teacher performance at HIKARI Vocational School, West Bandung Regency, as well as the principal's efforts to improve school management and increase the caliber of teacher performance at HIKARI Vocational School.  A descriptive approach and qualitative research methodology were used to write this scientific research.  The principal of Hikari Vocational School, the deputy head of curriculum and student affairs, and two teachers each served as research subjects.  This research uses documentation, interviews and observation as data collection methods.  First, research findings show that the principal of Hikari Vocational School applies a democratic leadership approach.  Second, the principal uses supervision as one of two strategies to improve the performance of his staff.